Text-Based Language Teaching Flipbook for Guest Relation Officer to Enhance Students Multimodal Literacy - Dewanthi, Fuji; Marsakawati, Ni Putu Era; Sari, Rima Andriani (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
This research aims to develop a flipbook for English for Guest Relations Officers. This research uses the Design and Development model by Richey and Klein (2014) as the basis for its methodology with ADDE steps.  The Design and Development Model has four stages, namely analysis, design, development and evaluation.  The data were obtained from this research used instruments in the form of interview guides, questionnaires and document analysis. This research involved twelve active participations of forth semester of English for Business and Professional Communication study program for the 2023/2024 academic year in Ganesha University of Education; one lecturer of English for Guest Relation Officers; and two practitioners work in the front office department at a five-star hotel in Bali. Data were analyzed qualitatively descriptively. In analyzing the data, the researcher used three concurrent flows of action proposed by Miles et al (2014), namely data reduction, data display, and conclusion or verification. The quality of the flipbook was assessed through a content validity test from ESP learning material and learning media experts. The evaluation showed that the flipbook was in accordance with the characteristics of ESP learning and was a good learning medium.